Metafysiske tegn: Skønlitteratur som religionsvidenskabeligt objekt - Liengaard, Inge (Religionsvidenskabeligt tidsskrift, 2003)
Analysing The Black Book, a novel by the contemporary Turkish writer Orhan Pamuk, this paper suggests that fiction can serve as an illuminating source in understanding one of the many roles that religion can play for modern man. Pamuk´s literary perspective is aesthetic and he disagrees with an essentialistic way of understanding and defining personal or cultural identity and cultural phenomena. In the novel he tries to create and describe alternative ways of conceiving reality. First and foremost by writing a novel without a fixed centre, but with many layers of undetermined meaning and persons with unclear, changing identities. Considering reality as chaotic and heterogenous he wants to avoid the common, monolitic descriptions of ‘tradition’, ‘modernity’, ‘East’ and ‘West’ and at the same time reintroduce elements long forgotten in the Turkish culture. It is at this point that Islam - or rather parts of the Islamic tradition - becomes interesting to Pamuk, who uses themes, metaphors and narrative structures especially from the Sufi-literature. Not only do these components present parts of a forgotten, but very rich, part of the Turkish culture, but the Sufi vocabulary and pictures are also useful vehicles to express the fluid and immaterial way of perceiving cultural as well as personal identities.